The Impact of Innovation Investment on the Performance of Chinese High-tech Enterprises - Regulatory Effect based on Debt Financing - Qiulan Yu,; Xiaodong Fu, (Journal of Theory and Practice in Humanities and Social Sciences, 2023)
High-tech enterprises are the leading agents of economic development, study the relationship between their innovation investment and enterprise performance, and guide enterprises to develop independent innovation strategies, improve independent innovation capabilities, and then promote China's further transformation into an innovative country. Major. Funds are the material basis for innovation investment. The cultivation and development of high-tech enterprises cannot be separated from the support of funds. As an important way of corporate financing, debt financing not only has the role of tax shield, but also can expand the financing channels of listed companies and optimize the allocation of financial resources. However, the credit financing of China's high-tech enterprises is generally at a low level. This paper finds through empirical research that debt financing has a negative adjustment effect on innovation investment and corporate performance, and further divides debt financing into corporate bonds, long-term and short-term loans and business. After credit, explore the different effects of the three on the innovation investment and performance of the enterprise, and finally draw conclusions and policy recommendations.